2004
DOI: 10.1002/chin.200412199
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Lactose‐Based S‐Linked Sialylmimetics of α(2,3)‐Sialosides.

Abstract: Carbohydrates Carbohydrates U 0500 Synthesis of Lactose-Based S-Linked Sialylmimetics of α(2,3)-Sialosides. -A new synthetic approach toward the synthesis of the title compounds from methyl β-D-lactoside in 11 steps is presented. -(LIAKATOS, A.; KIEFEL, M. J.; VON ITZSTEIN*, M.; Org. Lett. 5 (2003) 23, 4365-4368; Inst. Glycomics, Griffith Univ., Brisbane, Queensl., Australia; Eng.) -D. Singer 12-199

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…As carbohydrates are typically T‐cell‐independent B cell antigens, to generate high titers of anti‐glycan IgG antibodies, it is important to link the carbohydrates to an immunogenic carrier capable of activating helper T cells . We have previously demonstrated that bacteriophage Qβ is a powerful carrier to deliver tumor associated carbohydrate antigens .…”
Section: Resultsmentioning
confidence: 99%
“…As carbohydrates are typically T‐cell‐independent B cell antigens, to generate high titers of anti‐glycan IgG antibodies, it is important to link the carbohydrates to an immunogenic carrier capable of activating helper T cells . We have previously demonstrated that bacteriophage Qβ is a powerful carrier to deliver tumor associated carbohydrate antigens .…”
Section: Resultsmentioning
confidence: 99%